FINANCIAL INCLUSION AND AGRICULTURAL DEVELOPMENT IN INDIA - Choudhury, Semanti (International Journal of Research -GRANTHAALAYAH, 2018)
In most parts of the world, especially in the developing nations, the poor face challenges that impair their conditions and limit their opportunities. In order for growth to be inclusive, it should benefit all sectors of the economy while reducing the disadvantages faced by the poor and the underprivileged, as well as ensuring equitable opportunities for all economic participants. In the context of a developing country like India where a major portion of the population is dependent on agriculture for their livelihood, agricultural development forms an important part of any growth measure. One of the many alternative strategies for attaining inclusive growth is through developing an inclusive financial system. Financial inclusion is instrumental to facilitate economic transaction, manage day-to-day resources, protect against vulnerability, improve quality of life, make productivity-enhancing investments and leverage assets. However, in the Indian agricultural scenario, financial inclusion is faced by various impediments. This paper analyses the significance of financial inclusion and social sector expenditure in the rural economy in promoting agricultural development and inclusive growth in India, and infers with the help of a proposition made in a constructed general equilibrium model. It also offers certain policy prescriptions in this domain.